2010
DOI: 10.1163/156855109x434810
|View full text |Cite
|
Sign up to set email alerts
|

Low Velocity Impact Behavior of Aluminum Honeycomb Structures

Abstract: Impact behaviors of aluminum honeycomb sandwich panels (AHSPs) are investigated experimentally by using a drop weight test setup. The specimens of 12.7 mm cell size were tested by impacting at four different initial contact points, namely face center, corner, long edge and short edge of core cells, with two impactors of weights 5.25 kg and 11.9 kg, respectively. Dynamic nonlinear transient analysis was also carried out by a finite element simulation model developed based on continuum damage mechanics to accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…Specifically, the nature of failure will be determined by the point at which the projectile impacts in relation to the H/C cell. This observation was noted by Lee et al, where they concluded that impact behaviour is different depending on whether it occurs at the face, corner, short or long edges of the core cells (Lee et al, 2010). Of note, in regards to impact into spacecraft, unless the impact site is a radiator panel or solar array, most of the structure will be covered with MLI and this has been shown to help trap inside the satellite any small particles created during the harpoon impact (Reed and Barraclough, 2013).…”
Section: Debris Creationmentioning
confidence: 64%
“…Specifically, the nature of failure will be determined by the point at which the projectile impacts in relation to the H/C cell. This observation was noted by Lee et al, where they concluded that impact behaviour is different depending on whether it occurs at the face, corner, short or long edges of the core cells (Lee et al, 2010). Of note, in regards to impact into spacecraft, unless the impact site is a radiator panel or solar array, most of the structure will be covered with MLI and this has been shown to help trap inside the satellite any small particles created during the harpoon impact (Reed and Barraclough, 2013).…”
Section: Debris Creationmentioning
confidence: 64%
“…The basic strategy to model the individual damage mechanisms was to define the damage model for different components, respectively. To simulate the low velocity impact response of composite sandwich structure, the continuum damage mechanics based damage criteria were defined for predicting the intra-laminar damage of composite face sheet with delamination using cohesive zone elements while the mechanical behaviour of honeycomb core can be modelled, referring to the experimentally measured data (Aktay et al 2008;Liu et al 2017) or damage model for Nomex (Chen et al 2017;Liu et al 2015;Giglio et al 2012) or Aluminium honeycomb (Lee et al 2010;Kay 2003).…”
Section: Honeycomb Sandwich Structurementioning
confidence: 99%
“…Thanks to good mechanical properties and strong energy adsorption, aluminium honeycomb sandwich structures [1] have been extensively utilized in aerospace, protection, automobile, shipping and other fields. As a research hotspot, sandwich structure performance is mainly improved in three ways.…”
Section: Introductionmentioning
confidence: 99%